2014
DOI: 10.1371/journal.pone.0103698
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 (miR-21) Regulates Cellular Proliferation, Invasion, Migration, and Apoptosis by Targeting PTEN, RECK and Bcl-2 in Lung Squamous Carcinoma, Gejiu City, China

Abstract: BackgroundIn South China (Gejiu City, Yunnan Province), lung cancer incidence and associated mortality rate is the most prevalent and observed forms of cancer. Lung cancer in this area is called Gejiu squamous cell lung carcinoma (GSQCLC). Research has demonstrated that overexpression of miR-21 occurs in many cancers. However, the unique relationship between miR-21 and its target genes in GSQCLC has never been investigated. The molecular mechanism involved in GSQCLC must be compared to other non-small cell lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
134
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(146 citation statements)
references
References 45 publications
10
134
0
2
Order By: Relevance
“…Many studies have been conducted on the function of miR-21 in tumor occurrence and development. These studies showed that miR-21 could promote cell growth, proliferation, invasion and metastasis of various tumor cells by targeting PTEN, PDCD4, RECK, FASL and TIMP3 (38)(39)(40). Hiyoshi et al (41) found that the inhibition of microRNA-21 could lead to a reduction of the proliferation and invasion in esophageal squamous cell carcinoma cell lines by increasing PDCD4 protein expression With paired t-test performed to determine the significant difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have been conducted on the function of miR-21 in tumor occurrence and development. These studies showed that miR-21 could promote cell growth, proliferation, invasion and metastasis of various tumor cells by targeting PTEN, PDCD4, RECK, FASL and TIMP3 (38)(39)(40). Hiyoshi et al (41) found that the inhibition of microRNA-21 could lead to a reduction of the proliferation and invasion in esophageal squamous cell carcinoma cell lines by increasing PDCD4 protein expression With paired t-test performed to determine the significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…PDCD4, a tumor suppressor gene, was demonstrated to have low expression in various tumor tissues and cells (44,45). PDCD4, which was predicted to be a miR-21 target gene by TargetScan, has been reported to be a key regulator of tumor proliferation, apoptosis, adhesion, migration, invasion and metastasis (28)(29)(30)40,46). Tumor invasion is a multistep process in which cell motility is coupled with proteolysis and involves interaction of cells with extracellular matrix (ECM).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies have reported an association between XRCC1 Arg/Gln or Gln/Gln genotypes and the clinical response to chemotherapy in colorectal cancer (CRC) [4]. Huang et al [3] is involved in the development of malignant tumors through its effects on cell apoptosis, proliferation, invasion, and metastasis by targeting phosphatase, tensin homolog (PTEN), and tissue inhibitor of metalloproteinases 3 (TIMP3) or through its role in signaling pathways such as Wnt/β-catenin, PTEN/PI-3K/AKT, and RAS/ MEK/ERK [6,7]. Recent studies showed that miR-21 is frequently up-regulated in CRC and that elevated expression of miR-21 is associated with worse prognosis and inefficient response to chemotherapy [8,9].…”
Section: Kolorektal Karsinoması Olan Hastalarda Xrcc1 Gen Polimorfizmmentioning
confidence: 99%
“…The oncogenic activity of miR-21 on biological behavior of tumor cells is mainly by regulating downstream target genes (Xu et al 2014). Downstream target genes of miR-21 that have been experimentally confirmed include PDCD4, RECK, TIMP-3, and TPM1 which are involved in NSCLC, gastric cancer, cervical cancer, and colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%